Recovery of radio-cesium from actual high level liquid waste using solvents containing calix[4]arene-crown-6 ligands - Jagasia, P.; Dhami, P. S.; Mohapatra, P. K.; Ansari, S. A.; Jadhav, S. Y.; Kalyankar, G. K.; Gandhi, P. M.; Kharul, U. K. (Journal of Environmental Chemical Engineering, 2017)
This paper gives two methods, viz. a solvent extraction method and a hollow fiber contactor based liquid membrane method, for the separation of radio-cesium from actual high level liquid waste (HLLW) solutions using calix[4]arene-crown-6 based solvent systems. While the solvent extraction method involved calix[4]arene-bis-benzo-crwon-6 (CBC) in PTMS (phenyltrifluoromethyl sulphone), the hollow fiber supported liquid membrane method used a polysulphone fiber containing contactor and bis-octyl-benzo-calix[4]arene-mono-crown-6 (CMC) in 40% iso-decanol + 60% n-dodecane. Both methods reported selective radio-cesium separation with almost no contamination from the associated fission product radionuclides. The radiolytic stability of the hollow fiber contactor was checked by keeping the contactor module in contact with the diluted HLLW for 50 days. The second run carried out after 50 days resulted in excellent reproducibility suggesting efficacy of this method for radioactive waste remediation.
Keywords: 137Cs; Calix-crown-6; Cesium; fibers; Fission products; Hollow fiber contactor; Liquid membranes; liquids; PUREX-HLLW; Radioactive wastesSolvent extraction; solvent extraction; Solvents